2018
DOI: 10.3390/ma11091660
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Theory of Graphene Grain Boundaries

Abstract: The implementation of graphene-based electronics requires fabrication processes that are able to cover large device areas, since the exfoliation method is not compatible with industrial applications. The chemical vapor deposition of large-area graphene represents a suitable solution; however, it has an important drawback of producing polycrystalline graphene with the formation of grain boundaries, which are responsible for the limitation of the device’s performance. With these motivations, we formulate a theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Scattering theory of graphene grain boundaries has been formulated in Ref. [13][14][15][16][17] . In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scattering theory of graphene grain boundaries has been formulated in Ref. [13][14][15][16][17] . In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in Ref. 17 , it has been shown that, under appropriate circumstances, a grain boundary can be treated as a linear defect separating two regions with rotated crystallographic axes. The misorientation angle between the different sides of the junction has been taken into account by writing the Dirac equation within a rotated reference frame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is easy to show that Φ † + Φ − = 0 is a necessary requirement to get translational invariant solutions. Boundary conditions at x = 0 are implemented by using the matching matrix method in the form Ψ(0 + , y) = MΨ(0 − , y), with the matching matrix M directly derived from the interface potential according to the relation M = exp(−iσ x B + /( v)) [20]. Inspection of the boundary conditions shows that the quantum state we are talking about nucleates at the interface provided that M 11 = 0, i.e.…”
mentioning
confidence: 99%
“…Moreover, following [20], it can be shown that the interface potential of a grain boundary junction with rotated crystallographic axes retains a dependence on the misorientation angle. According to this observation, we expect that in graphene grain boundaries the renormalized modes velocity v ef f can be controlled by the misorientation angle between the crystallographic axes of the two sides of the junction.…”
mentioning
confidence: 99%